Cartilage proteoglycan aggrecan epitopes induce proinflammatory autoreactive T-cell responses in rheumatoid arthritis and osteoarthritis. Issue 01 (12th February 2009) - de Jong, H; Berlo, S E; Hombrink, P; Otten, H G; van Eden, W; Lafeber, F P; Heurkens, A H M; Bijlsma, J W J; Glant, T T; Prakken, B J
Abstract : Objectives: To explore potential T-cell epitopes of the core protein of human cartilage proteoglycan aggrecan (PG) in patients with rheumatoid arthritis (RA) or osteoarthritis. Methods: Peptide-specific T-cell proliferation and cytokine/chemokine production in response to PG-specific peptides were measured in RA and osteoarthritis patients and in healthy controls. Results: Peptides representing amino acid regions 16–39 and 263–282 of PG were most frequently recognised by T cells in a subset of patients with RA or osteoarthritis. Peripheral blood mononuclear cells from these PG-reactive RA and osteoarthritis patients showed increased production of proinflammatory cytokines/chemokines in response to PG peptide stimulation. As PG p263–282 was found to show high sequence homology with Yersinia Yop protein, the corresponding bacterial (Yersinia) peptide was also tested. Remarkably, RA and osteoarthritis patients responding to the Yersinia peptide also responded to p263–282 of PG suggesting a possibility of molecular mimicry in these patients. Conclusions: These results indicate that PG-specific peptides, located in the G1 domain of PG, can induce (auto)antigenic T-cell responses in RA and osteoarthritis patients. These peptides might thus be involved in the immune pathogenesis and/or cartilage degradation in RA and osteoarthritis.